The Impact of Organizational Silence on Turnover Intention - Ercan Öge (Sosyal Siyaset Konferansları Dergisi)
One of the negative consequences of organizational silence on employees is its impacts on their turnover intentions. This fact makes it important to investigate the antecedent that caused the turnover intention. The purpose of this study is to investigate the impact of organizational silence on employees’ turnover intentions their jobs and aims how this impact can be modelled. Considering the limited number of studies in the literature regarding the relationship between organizational silence and turnover intention, with this study it has been tried to contribute to the literature in this direction. The sample of the study, which has been conducted with the causal survey model, consists of 107 people, working in a plastics enterprise, which carries on its operations in Büyükçekmece district of Istanbul. As a result of the study, it has been found that there is a high level of significant correlation between organizational silence and turnover intention. It hasbeen found significant that organizational silence predicts the turnover intention. Demographic differentiations of turnover intention and organizational silence have not been found significant.